Jurisdiction and powers of the civil courts - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
When the court has appellate jurisdiction, it may only review the proceedings of the trial court. Generally, some of the above-mentioned courts are conferred with only original jurisdiction while others have several types of jurisdiction such as original, appellate, supervisory and revisionary, referential and advisory jurisdictions. Some courts may have specialised jurisdiction to only hear certain matters